What Color is My Arm? Changes in Skin Color of an Embodied Virtual Arm Modulates Pain Threshold - Martini, Matteo; Pérez Marcos, Daniel; Sanchez-Vives, Maria V. (Frontiers in Human Neuroscience, 2013)
It has been demonstrated that visual inputs can modulate pain. However, the influence of skin colour on pain perception is unknown. Red skin is associated to inflamed, hot and more sensitive skin while blue is associated to cold. We aimed to test whether the colour of the skin would alter the heat pain threshold. To this end, we used an immersive virtual environment where we induced embodiment of a virtual arm that was co-located with the real one and seen from a first person perspective. Virtual reality allowed us to dynamically modify the colour of the skin of the virtual arm. In order to test pain threshold, increasing ramps of heat stimulation applied on the participants’ arm were delivered concomitantly with the gradual intensification of different colours on the embodied avatar’s arm. We found that a reddened arm significantly decreased the pain threshold compared with normal and bluish coloured skin. This effect was specific when red was seen in the arm, while seeing red in a spot outside the arm did not decrease pain threshold. These results demonstrate an influence of skin colour on pain perception. This top-down modulation of pain through visual input suggests a potential use of embodied virtual bodies for pain therapy.